2015
DOI: 10.1097/mao.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cholesteatoma Surgery Using a Single-Staged Canal Wall Down Approach

Abstract: The use of a CWD approach with obliteration of the mastoid cavity to surgically treat extensive cholesteatoma in children results in a low recurrence rate and high rate of a trouble-free ear in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
(6 reference statements)
1
25
0
1
Order By: Relevance
“…We selected surgical techniques depending on the extension of the lesion. If it is necessary to eradicate the cholesteatoma, canal wall-down tympanoplasty and mastoid obliteration may be selected as described in previous reports [16,17]. Compared with previous reports [6,[16][17][18], our case management was relatively good in both the CC and AC groups.…”
Section: Discussionmentioning
confidence: 66%
“…We selected surgical techniques depending on the extension of the lesion. If it is necessary to eradicate the cholesteatoma, canal wall-down tympanoplasty and mastoid obliteration may be selected as described in previous reports [16,17]. Compared with previous reports [6,[16][17][18], our case management was relatively good in both the CC and AC groups.…”
Section: Discussionmentioning
confidence: 66%
“…Most authors have reported inferior outcomes in children compared with the adult cholesteatoma patient population regarding residual and recurrent disease (3)(4)(5)(6)(7)(8)(9). Various studies regarding CWU techniques in children without obliteration (3)(4)(5)(6)(7)(8)(9)(10) reported inferior results concerning residual and recurrent rate compared with the obliteration techniques (16)(17)(18)(19)(20). In our adult population, the single-stage CWU-BOT technique with TOA reconstruction also markedly improved the results concerning safety.…”
Section: Discussionmentioning
confidence: 83%
“…Arguments to use the CWU-BOT technique in extensive cholesteatoma in children are as follows: 1) the unsatisfactory residual and recurrent rates in our own pediatric population using the CWU technique without obliteration, as compared with the CWD technique (8); 2) the good hygienic and functional results in CWU populations (3)(4)(5)(6)(7)(8)(9), 3) the introduction of the non-EP DW MRI for follow-up of the obliterated mastoid and epitympanic space (15), 4) the rewarding results of the CWU-BOT in adults (12), and 5) convincing good results with obliteration reported by other authors (11,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…187 Mastoid obliteration with 1-stage eradication of the disease and a total reconstruction procedure provide long-term hearing improvement with a low incidence of persistent or recurrent disease in adults and children. [195][196][197][198][199][200][201][202][203] A quality-oflife study 204 conducted on patients with cholesteatoma who underwent mastoidectomy and mastoid obliteration with autologous cranial bone graft indicated a significant quality-oflife benefit from the procedure. Csakanyi et al 205 constructed a mathematical model that predicted that mastoid obliteration can improve ME gas pressure balance, resulting in better long-term outcome in MEs with poor mastoid pneumatization and ETD.…”
Section: Physiology and Pathophysiologymentioning
confidence: 99%